Working Memory Training in Norwegian Children with Cerebral Palsy (CP) Show Minimal Evidence of Near and No Far Transfer Effects. - Beneventi, Harald; Løhaugen, Gro CC; Andersen, Guro L; Sundberg, Cato; Østgård, Heidi Furre; Bakkan, Ellen; Walther, Geir; Vik, Torstein; Skranes, Jon (Developmental Neurorehabilitation)
In children with cerebral palsy (CP), learning disabilities are well documented, and impairments in executive functions, such as attention, inhibition, shifting and working memory, represent significant burdens on patients, their families and the society. The aim of this study was to evaluate whether Cogmed RM working memory training could improve working memory in children with CP and investigate whether increased working memory capacity would generalize to other cognitive functions. Twenty-eight children completed the training and the results were compared to a waitlist control group (n = 32). The results yielded three main findings. First, children with CP improved with practice on trained working memory tasks. Second, the intervention group showed minimal near transfer effects to non-trained working memory tasks. Third, no effects on cognitive and behavioral far transfer measures were found.